2007
DOI: 10.1007/s11938-007-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

Sedation of the pediatric and adolescent patient for GI procedures

Abstract: There remains no ideal sedative for pediatric and adolescent patients undergoing gastrointestinal procedures. Instead, pediatric gastroenterologists must consider many factors, including patient age, medical history, clinical status, anxiety level, as well as targeted sedation level, to select the appropriate methods and agents to achieve optimal sedation for endoscopy. The two primary types of sedation are endoscopist-administered intravenous (IV) sedation and anesthesiologist-administered general anesthesia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
0
10
0
1
Order By: Relevance
“…6 The authors conclude that the use of general anesthesia may be safer than procedural sedation for the treatment of pediatric patients with burn; however, there is no direct evidence to suggest this, as the studies quoted to favour the use of general anesthesia over procedural sedation have been conducted in patients undergoing sedation for imaging or endoscopy. 6 -9,13…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 The authors conclude that the use of general anesthesia may be safer than procedural sedation for the treatment of pediatric patients with burn; however, there is no direct evidence to suggest this, as the studies quoted to favour the use of general anesthesia over procedural sedation have been conducted in patients undergoing sedation for imaging or endoscopy. 6 -9,13…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of general anesthesia for the application of burn dressings in the OR has been shown to be associated with few adverse events 6 ; however, it may not be practical for the dressing or physiotherapy component. There is some evidence to suggest that general anesthesia compared to sedation may be safer in children, [6][7][8][9] but the majority of these studies comparing sedation and general anesthesia were reported for pediatric gastrointestinal procedures. 7,9 Although there is literature supporting outpatient burn care, 1,2 specific data on the safety of the outpatient sedation component are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While many pediatric endoscopists report performing all of their procedures with general anesthesia, approximately a third continue to report administering moderate sedation [2] using a variety of endoscopist-administered sedation regimens [3, 4]. Many institutions use a sedation regimen that combines a narcotic with a benzodiazepine.…”
Section: Introductionmentioning
confidence: 99%